2014
DOI: 10.2105/ajph.2014.301928
|View full text |Cite
|
Sign up to set email alerts
|

State Firearm Laws, Firearm Ownership, and Safety Practices Among Families of Preschool-Aged Children

Abstract: Objectives. We investigated how state-level firearms legislation is associated with firearm ownership and storage among families with preschool-aged children. Methods. Using 2005 nationally representative data from the Early Childhood Longitudinal Study-Birth Cohort (n = 8100), we conducted multinomial regression models to examine the associations between state-level firearms legislation generally, child access prevention (CAP) firearms legislation specifically, and parental firearm ownership and storage safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…There are wide state-specific variations that are further complicated by additional firearm laws that could be either restrictive or permissive [14]. The declining pediatric FH rates mainly driven by reduction in unintentional injuries and the higher rates among African American as compared to White children sustaining assault injuries found in our study, indicates the relevance of socio-demographic factors.…”
Section: Implications For Health Services and Policy Makersmentioning
confidence: 61%
“…There are wide state-specific variations that are further complicated by additional firearm laws that could be either restrictive or permissive [14]. The declining pediatric FH rates mainly driven by reduction in unintentional injuries and the higher rates among African American as compared to White children sustaining assault injuries found in our study, indicates the relevance of socio-demographic factors.…”
Section: Implications For Health Services and Policy Makersmentioning
confidence: 61%
“…Third, we measured state firearm legislation using the Brady score, a comprehensive scoring system that has been used in similar studies but not validated. 20,21,53 To our knowledge, there are no validated scales to compare firearm legislation between states, and although the Brady score assigns equal points to states on the 57 and would not account for the 10 times variation in discharge rates we observed between states. Lastly, these findings are vulnerable to misclassification bias because we could not identify injury victims who were transferred across state lines for treatment.…”
Section: Limitationsmentioning
confidence: 92%
“…Furthermore, studies have found that a child is 100 times more likely to die of a gunshot if he lives in MO, USA as opposed to Ontario, Canada [1] and that children in the USA are nine times more likely to die from a gun than most other industrialized nations [9]. While this increased risk is likely to be due to a multitude of factors, it seems societal differences influence the firearm-related statistics significantly [10]. Furthermore, those statistics say nothing of the many firearm-related deaths that are attributed to self-harm or accidents that occur in the USA each year [3,11].…”
Section: The Rate Of Firearm-related Violencementioning
confidence: 99%
“…Yet, it remains largely unknown if the Child Access Protection (CAP) laws decrease the accidental death of children related to firearms [8,24]. While the American Academy of Pediatrics recommends that parents who own firearms keep them in a locked safe [10] and CAPs make it illegal to store a gun in a place that is easily accessible to children [1], many children continue to have access to firearms. At least one firearm is kept loaded and unlocked in 20-50 % of all households with a firearm [25].…”
Section: Children and Firearmsmentioning
confidence: 99%
See 1 more Smart Citation